Staphylococcus aureus: Superantigens and Autoimmunity - França, Thais Graziela Donegá [UNESP]; de Lourdes Ribeiro de Souza da Cunha, Maria [UNESP] (My University, 2021)
Staphylococcus aureus is one of the most prevalent pathogens in the human population. S. aureus exhibits several escape mechanisms that allow it to evade host defenses. The main evasion mechanisms include inhibition of neutrophil chemotaxis; release of toxins that kill leukocytes; resistance to phagocytosis, complement system inactivation and production of several toxins defined as superantigens (SAgs). These toxins can activate a high proportion of T cells due to their ability to bind to both MHC class II molecules in antigen presenting cells and specific Vβ regions in the T cell receptor. This activation results in the polyclonal stimulation of T cells and an elevated production of proinflammatory cytokines. Bacterial superantigens are potent T cell activators that can activate T cells with specificity for antigens of the central nervous system. Experimental and epidemiological evidence support the theory that S. aureus that produces SAgs may be implicated in the genesis of Multiple sclerosis, septic arthritis, lupus and others autoimmune diseases. Multiple sclerosis is a demyelinating disease of the central nervous system, which is mainly mediated by T cells that are specific for the myelin self-antigen. These auto reactive T cells are generated in the periphery and cross the blood-brain barrier to the brain parenchyma where they initiate an autoimmune attack on the myelin sheath. Infectious disease agents can modulate autoimmune diseases in many different ways, such as triggering these pathologies or, contrarily, preventing their development. This chapter aims to describe about staphylococcal superantigens and the effect SAgs in the development of autoimmune diseases.